The efficacy of vancomycin-loaded biphasic calcium phosphate bone substitute in the promotion of new bone growth and the prevention of postoperative infection - Wang, Shi-Yong; Yao, Ru-Bin; Yang, Kai-Shun; Liang, Huang-Chien; Su, Chen-Ying; Fang, Hsu-Wei; Lim, Sher-Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Due to the increasing need for suitable alternatives to bone grafts, artificial bones made of biphasic calcium phosphate (BCP) are currently being extensively researched. These porous bone substitutes have also demonstrated considerable incorporation with the host bone, and new bone is able to grow within the porous structure. They therefore offer a potential therapeutic approach for bone defects. Methods: Vancomycin-loaded BiceraTM, a BCP bone substitute, was investigated in order to prevent implant-associated osteomyelitis and postoperative infection after orthopedic surgery. The loading capacity of BiceraTM was measured to understand its potential antibiotic adsorption volume. An antibiotic susceptibility test was also carried out to analyze the effect of BiceraTM loaded with different concentrations of vancomycin on the growth inhibition of methicillin-resistant Staphylococcus aureus (MRSA). Vancomycin-loaded BiceraTM was implanted into rabbits with bone defects, and general gross, radiographic, and histological evaluation was undertaken at 4, 12, and 24 weeks after implantation. Results: The maximum loading capacity of vancomycin-loaded BiceraTM was 0.9 ml of liquid regardless of the vancomycin concentration. Antibiotic susceptibility tests showed that vancomycin-loaded BiceraTM inhibited the growth of MRSA for six weeks. In addition, animal studies revealed that new bone grew into the vancomycin-loaded BiceraTM. The percentage of new bone formation from 4 to 24 weeks after implantation increased from 17% to 36%. Conclusions: Vancomycin-loaded BiceraTM could effectively inhibit the growth of MRSA in vitro. It was found to incorporate into the host bone well, and new bone was able to grow within the bone substitute. The results of this study indicate that vancomycin-loaded BiceraTM is a potential bone substitute that can prevent implant-associated osteomyelitis and postoperative infection.